THE EFFECT OF TRAINING AND EDUCATION LEVELS ON THE COMPETENCY OF GRADUATE PARTICIPANTS AT LPK ANANDA PERKASA MULIA - Risza Putri Elburdah (BAIK Publishers, 2024)
The purpose of this study was to determine the effect of training and education levels on the competency of graduate participants at LPK Ananda Perkasa Mulia. The research method used in this study uses a quantitative approach. The population is 50 people. The sampling technique uses saturated samples so that the number of samples in this study is 36 respondents. The data analysis technique uses simple linear regression. The results of the study show that there is a positive and significant effect of the effect of training and education levels on the competency of graduate participants at LPK Ananda Perkasa Mulia. This is evidenced by the f-count value > f-table, which is 34.805 > 3.20, the probability value (significance) = 0.000.